ChemInform Abstract: Aluminum‐Catalyzed Oxazolidinone Synthesis and Their Conversion into Functional Non‐Symmetrical Ureas. Issue 5 (January 2016) - Laserna, Victor; Guo, Wusheng; Kleij, Arjan W.
Abstract: The Al‐catalyzed reaction of epoxides with phenyl carbamate affords stereoselectively oxazolidinones, which are readily transformed into non‐symmetrical ureas by reaction with amines.